2007
DOI: 10.1002/mus.20784
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit number estimates and quantitative motor unit analysis in healthy subjects and patients with amyotrophic lateral sclerosis

Abstract: Limitations associated with global measures of function in patients with amyotrophic lateral sclerosis (ALS) and the qualitative nature of needle electromyography have stimulated the development of alternate means of monitoring disease severity and progression in ALS. Thus, the objective of this study was to examine the ability of one these techniques, decomposition-based quantitative electromyography (DQEMG), to obtain electrophysiological data, including motor unit number estimates (MUNEs), from a group of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…[12][13][14][15] These EMG signals were decomposed into MUP templates using DQEMG. 16 DQEMG typically finds 51 isolated MUPs produced by a single motor unit, aligns them, and uses a median trimmed average to form the MUP template.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15] These EMG signals were decomposed into MUP templates using DQEMG. 16 DQEMG typically finds 51 isolated MUPs produced by a single motor unit, aligns them, and uses a median trimmed average to form the MUP template.…”
Section: Methodsmentioning
confidence: 99%
“…The recruitment and rate coding strategy varies among muscles, and is seemingly dependent on the number of motor units and the function of the muscle. In the Wrst dorsal interosseous (FDI), for example, it is suggested that there are approximately 144 motor units, and evidence suggests that all of these motor units are typically recruited by approximately 60% maximal voluntary contraction (MVC) force (Boe et al 2007). Beyond 60% MVC in the FDI, rate coding is used to increase force.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond 60% MVC in the FDI, rate coding is used to increase force. In the biceps brachii, it is estimated that there are between 271 and 360 motor units, and it is suggested that new motor units are recruited up to approximately 88% MVC (Boe et al 2007;Kukulka and Clamann 1981), relying solely on the rate coding for only approximately the highest 10-20% of MVC.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically this information is valuable in that it provides insight into the changes occurring at the level of the MU in response to disorders of the neuromuscular system. Evidence to support this has come from several studies, including the observation of decreased MU number estimates and increased MU size and complexity in patients with amyotrophic lateral sclerosis (ALS) (Boe et al, 2007) and Charcot-Marie Tooth (CMT) disease (Shy et al, 2007), in addition to demonstrating age-related MU remodeling and an associated decrease in the estimated numbers of MUs in old and very old men (McNeil et al, 2005).…”
Section: Introductionmentioning
confidence: 91%